Estrategias de intervención para disminuir factores de riesgo en paludismo falciparum en la población de San Lorenzo - Morillo Revelo, Wilmer Patricio (2017)
This study also found that the people had to be informed about the supervision and vectorial control; the knowledge of malaria is critical in the Kennedy community. This investigation will help to reduce the number of people with malaria which is rated to 24.4 cases per 10000 people in the Canton San Lorenzo. A descriptive - correlational study was carried out, using a qualitative and quantitative method using the survey and the interview to determine the level of knowledge. The surveys and interviews showed that 68% of the people who work in the health sector don't know the basic concepts of malaria and 73% have not been trained in vigilance and vectorial control. Moreover, inside the Kennedy community less than 36% of its population know what is malaria. Other results indicated that $2 is the percentage of nursing assistants who know about malaria; while only 10% of administrative personnel know about it. Likewise about 70% of the population in the community completed high school and 37% work in fishing activities. After the preventive strategies were implemented a new survey was done. In this case, 98% of the people knew about the malaria's new regulation and 95% confirmed to know theoretical and practical methods of prevention, concluding that the adopted strategies improved the situation of control and epidemiological surveillance of malaria in the population.